THE TREND OF BIRTH RATE AND SOME FACTORS ASSOCIATED WITH HIGH FERTILITY IN WEST AZERBAIJAN, IRAN - A. Nadim; Sh. Salarilak (Tehran University of Medical Sciences, 2000)
In order to determine the exact birth rate and also percent of birth - orders in all births in the province of west Azerbaijan, all centres of birth registration in the province were asked to fill a questionnaire at the time of issuing identity document for children. In the questionnaire, parents were asked to mention the place of birth, sex and birth order of the children and also the occupation and education of the mother and the father. This study was carried out in 1996. During this year the population of the province was 2495343. The number of all registered birth was 43833. This study showed that the birth rate in the province has declined from 40.8 per thousand in 1986 to 17.6 per thousand in 1996. Male/Female ratio varied from 100 to 111 in different districts, the average was 108. The birth order of 401 male was higher in Kurds as compared to Azaris. This may be secondary to the effect of education because the study showed that the higher the education of mother or even father, the less is the probability of birth order of more than 3. The main recommendation is more emphasis on the female education to reduce the birth rate to the optimum level.